2012
DOI: 10.1039/c2jm35080g
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline 21,23-dithiaporphyrins

Abstract: Meso-substituted 21,23-dithiaporhyrins were synthesized that self-assemble into columnar liquid crystalline phases. Furthermore, the porphyrins possess absorption profiles that span from 400 nm to 800 nm, undergo two reversible electrochemical redox reactions at approximately 465 and 670 mV vs. ferrocene/ferricenium and are electrochromic. Thin films of these dithiaporhyrins of approximately 60 nm thickness were formed by spin-casting methods from chloroform and were subjected to impedance spectroscopy. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…Typically, porphyrins with less than four meso -arylethynyl substituents are synthesized via reaction of TIPS-propynal and subsequent Sonogashira cross-couplings. , Dithiaporphyrin synthesis involves a synthetic route from 2,5-thiophene diols, , shown in Scheme , prior to the final macrocyclic ring-closing step. This diol formation synthetic step permits a cleaner macrocyclization reaction, resulting in easier purification because scrambling is largely suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, porphyrins with less than four meso -arylethynyl substituents are synthesized via reaction of TIPS-propynal and subsequent Sonogashira cross-couplings. , Dithiaporphyrin synthesis involves a synthetic route from 2,5-thiophene diols, , shown in Scheme , prior to the final macrocyclic ring-closing step. This diol formation synthetic step permits a cleaner macrocyclization reaction, resulting in easier purification because scrambling is largely suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the following derivatives were synthesized: one with a weakly electron-donating alkyl group and one with a strong electron-donating ether group. Scheme S1 (see Supporting Information (SI)) shows the synthetic details, which afforded the ethynyl precursors 1a and 1b that were previously reported. , Briefly, the synthesis of the strong electron-donating substituent begins by alkylating 4-bromophenol as described in our previous synthetic work , to obtain 1-bromo-4-(dodecyloxy)­benzene. The weakly electron-donating 1-bromo-4-dodecylbenzene was obtained by a Friedel–Crafts acylation of bromobenzene with dodecanoyl chloride followed by a Wolff–Kishner reduction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More exotic porphyrins were published by Sessler, prepared a cyclo[8]­pyrrole, which was nonmesomorphic, but showed broad Col h phases upon complexation of TNF, trinitrobenzene, trinitrotoluene, or picric acid . 21,23-Dithiaporphyrins with Col r and Col h phases, exhibiting electrochromic properties, were described by Bromby et al Thin films of these materials generated by spin-casting showed an increase of the conductivity by 4 orders of magnitude upon electrochemical p-doping, making them interesting candidates for organic photovoltaics.…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…[6] Oligothiophene derivatives end-capped with alkyl chains, show liquid crystalline properties, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and prefer to self-organize into supramolecular ordered layered structures:t hey display two-dimensional charge transport mobility comparable to inorganic semiconductors of amorphous and polycrystalline silicon, and have been investigated as active materials in organic field-effect transistors (OFET). [21][22][23][24][25] Discoticl iquid crystals (DLCs) [26][27][28][29] that contain afused-thiophene unit [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] are also attractive candidates as novel organic semiconductors owing to their advantageous combination of the highly applicable and promising electronic properties of the thiophene moiety and the propensityo fD LCs to self-organize into ac olumnar mesophase for one-dimensional charget ransportp athways. [26] However,t he number of thiophene-containing DLCs is still limited compared with the numerousr od-like liquid crystalsi ncorporatin...…”
Section: Introductionmentioning
confidence: 99%